Academic Stereotypes of African American Female Student-Athletes: A Qualitative Study - Bruening, Jennifer E. (My University, 2005)
Greendorfer (1993) described stereotypes as "extremely powerful and potent" fonns of discrimination (p. 5). This study examined how stereotypes affected 12 African American female collegiate student-athletes at a large Midwestern university. Data were collected through both focus group and individual interviews during the 1998-1999 academic year. One of the central themes identified by the participants was academic stereotypes and within theme, two subthemes emerged. The first subtheme was labeled overlooking and lowered expectations (Perlmutter, 2003) and further defined as "attending college only because of athletics." The second subtheme was labeled isolation and further defined as "being the only African American in your classes" with additional isolating effects of gender and racial stereotypes also discussed.
Keywords: race; sex/gender; demographics